Isolation and Characterization of Cellulolytic Pseudomonas Aeruginosa from Teak Forest Soil for its Cellulase Production and Cellulolytic Activity (Chittagong University Journal of Biological Sciences, 2024)
A cellulolytic bacterium was isolated from Tectona forest soil and provisionally identified as Pseudomonas aeruginosa. The bacterium showed the highest level of reducing sugar and extracellular protein production when incubated for 3 days at 40°C, pH 8.5 in Winstead’s broth having 1.5% carboxymethyl cellulose (CMC) and 0.2% Yeast Extract as carbon and nitrogen sources, respectively. The bacterium produced the maximum 462 µg/ml reducing sugar and 450 µg/ml extracellular proteins. Crude cellulase produced by the bacterium showed the highest carboxymethyl cellulase (CMCase) activity rather than filter paperase (FPase), Avicelase and β-Glucosidase activities. The crude cellulase showed highest CMCase activity when incubated for 90 minutes at pH 8.5, 25°C using CMC and Yeast Extract as carbon and nitrogen sources, respectively as well as in presence of Hg2+ ion and SDS (inhibitor and reductant). The highest enzyme activity was found to be 315 U/ml. The molecular weight of the crude cellulase was found as 33 kDa through SDS PAGE analysis. According to Worthington Enzyme Manual it may be Endoglucanase IV.The Chittagong Univ. J. B. Sci., Vol. 10(1 &2):167-179, 2020